Inclusão e Educação de Jovens e Adultos: conflitos no agir do professor de Língua Inglesa - Bezerra , Magna Rafaela de Sousa e Silva (2020)
Based on Applied Linguistics, this study addresses the teaching action in the light of Sociodiscursive Interactionism (BRONCKART,1999), because this current considers language as a central role in the development of human activities, thus offering us categories of analysis that can take into account the acting as a language for individuals through text analysis. Because it is considered a transdisciplinary current that sometimes dialogues with Applied Linguistics, sometimes with other areas, we also use the Sciences and Psychology of Work to help us compose our theoretical contribution, in order to help us better understand the work of the teacher as a true work (MACHADO,2009;CLOT, 2010). We were interested in investigating how an English Language teacher in the Youth and Adult Education modality understands her acting in a classroom, in addition to all the existing adversities (students with different age groups, students who are late duetowork, etc.), with two visually impaired students. Thus, we plan to search for voices and modalities to understand the way the teacher textualizes her teaching behavior in face of possible conflicts in the EJA classroom.The corpus was collected using a method from the Clínica da Activity (CLOT, 2010), simple self-confrontation, which provides for recording the worker at his working time and then is scheduled for the worker to watch the video and make comments about it of your action. It is the worker's comments that we take into account for our analysis.The analysis indicated that although the teachers responsible most of the time for the inclusion and permanence of students in the classroom, sometimes she shows indignation that this attitude does not come from all her colleagues. We also found that sometimes the teacher tries to share the responsibility for creating material, for example, with students with visual impairments, since not only them, but all their students directly impact their teaching behavior. In addition,we can see that from the modalities found, the teacher shows concern to keep all students included and tries to create an inclusive space. We also emphasize that from the managed conflicts it manages to promote its development, since these conflicts act directly under its labor.